Acquired von Willebrand syndrome in a patient with small lymphocytic lymphoma and Sjögren's syndrome: which associated condition should be prioritized?. Issue 5 (July 2019) - Pardos-Gea, José; Martínez, Fernanda; Abrisqueta, Pau; Santamaría, Amparo; Bosch, Francesc
Abstract : N/A: Acquired von Willebrand syndrome (AVWS) is a rare hemorrhagic condition that poses both a diagnostic and a therapeutic challenge. Here we report a singular case of AVWS with two associated conditions, small lymphocytic lymphoma (SLL) and Sjögren's syndrome. The patient presented with recurrent and severe digestive bleeding that forced us to raise a curative attempt of AVWS. A first immunosuppressive therapy with immunoglobulins was unsuccessful and it was later decided to treat lymphoproliferative entity with bendamustine and rituximab effectively achieving SLL and AVWS remission. On the basis of our case and through literature review, we discuss potential strategies to achieve AVWS remission when it appears in the setting of several causative associated conditions.